Computational analysis of subsonic jets from round and bevelled nozzles. (2017) - Sandhya, M.; Tide, P.S.
Numerical simulations of turbulent compressible subsonic jets at Mach number 0.75 emanating from round and bevelled nozzles were carried out using a commercially available CFD code. The modelling and calculations were performed on a three-dimensional computational domain using RANS equations and SST k-ω turbulence model. The computational domain was discretised using hexahedral/tetrahedral mesh with approximately two million cells. The flow was investigated for axial and radial profiles of velocity components, shear layer thickness, self preserving nature, turbulent intensity, turbulent viscosity and Reynolds's stresses. The results were found to be in reasonable agreement with the available data in the literature. It was observed that the bevelling of nozzle can significantly change both flow pattern and turbulence structure and thus act as a passive method for jet noise reduction. Moreover, flow characteristics of jets issuing from various nozzle configurations intended to reduce noise levels may be easily evaluated using this computationally less expensive method.